Design and building of a battery charging system using hybrid solar tracker and electric trip based on FPAO-FLC - Abadi, Imam; Musyafa, Ali; Erwandha, Kevin Gica; Fitriyanah, Dwi Nur (Institute of Advanced Engineering and Science, 2022)
The proposed system is a hybrid charging system between a solar tracker and an electric grid using two converter types. The photovoltaic (PV)-based solar tracker has powerful tools, but its weakness is when the absence of sunlight. With a combination of two resources, the weakness can overcome. The control so good is needed so that it can overcome those weaknesses too. This study uses the flower pollination algorithm optimization-fuzzy logic controller (FPAO-FLC). Results of control using FPAO-FLC has a value of a rising time of 0.0123 seconds, settling time of 2.1099 seconds, maximum overshoot of 6.08%, a peak time of 0.9246 seconds, and steady-state error of 3.43%. The efficiency of the ZETA converter using FPAO-FLC control in the tracking condition PV compared to the fixed condition has increased 43, 24%, and the state of charge (SOC) of the battery reaches 39.08%. The advantage of the hybrid system is that it offers two automatic operating modes, namely simultaneous and individual. The average total energy obtained from the automatic dual supply mode charging process is 482.86 Wh with a battery SOC reaching 83.9%.